Evaluation of analgesic, antioxidant and cytotoxic activities of ethanol extract of Clerodendrum viscosum Vent - Das, Sujan Chandra; Kuddus, Md. Ruhul; Qais, Nazmul; Hasan, Choudhury M. (Journal of Applied Pharmaceutical Research, 2021)
Clerodendrum viscosum Vent. is a very common plant in Bangladesh which is locally familiar as “Bhat” or “Ghetu”. Here, the ethanol extract of whole plant part of C. viscosum and its various solvent (petroleum-ether, chloroform and ethyl acetate) fractions were subjected for the appraisal of analgesic, antioxidant and cytotoxic activities. Analgesic activity was tested by acetic acid-induced writhing model in Swiss albino mice. All the plant samples at the oral doses of 100- and 200 mg/kg body weight were found to exhibit significant (p<0.05) pain reducing activity in test animals. Highest inhibition of writhing was 62.38% by the ethyl acetate soluble fraction at dose of 200 mg/kg body weight while the standard drug diclofenac sodium (50 mg/kg) produces 76.14% reduction of abdominal writhing. DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical quenching assay was employed to determine the antioxidant potential of the plant samples while cytotoxic activity was checked by brine shrimp lethality bioassay. In DPPH radical scavenging assay, the plant samples showed prominent antioxidant activity. Among all, the ethyl acetate fraction showed maximum antioxidant potential with IC50 value of 28.02±0.53 μg/ml. In cytotoxic assay, the petroleum-ether fraction demonstrated strong cytotoxicity with LC50 value of 1.42±1.12 μg/ml. In summary, C. viscosum extracts possess significant analgesic, antioxidant and cytotoxic activities which rationalize its traditional use in folk medicine.